Oltre la globalizzazione: le proposte della Geografia economica Giornata di Studio della Società di Studi Geografici. Firenze 14 ottobre 2011 - Randelli, Filippo; DINI, FRANCESCO (Firenze University Press, 2012)
In 1980 Froebel, Heinrichs and Kreye published the English-language The New International Division of Labour, trying to highlight the consequences of market reorganization after the crisis of the mid 1970s, which was soon to transform into so-called globalization. A third of a century later, the "fantastic adventure" of market integration seems to have been crystallized by the 2007-2008 crisis, opening a further period of great instability. But the geography of wealth production has transformed radically and appears unrecognizable to the early-80s scholar. In a framework of great social, political and cultural change, China, a country at the time defined as an "economic dwarf", is the second largest economy on the planet and has become its "factory". The standardizing concept of "Third World" having vanished, some former colonial economies have undertaken rapid growth processes, while others have ruinously accentuated their underdevelopment. The traditionally advanced regions, then defined as "industrial", have opened out into trajectories defined, vice versa, as "post-industrial", some consolidating their competitive edge and others sparking lengthy declines.